P2P file sharing app for android devices sporting IEEE802.15.4 zigbee radios - Abd Rahman, Akmal Nurhananie; Habaebi, Mohamed Hadi; Ismail, Mahamod (2014)
This paper introduces the idea of interfacing Zigbee modem with Android platform to provide a communication infrastructure for a peer-to-peer (P2P) file sharing protocol that was developed specifically for the Zigbee air interface channel. It involves devices with Android 4.0 (Ice Cream Sandwich), which is the lowest version of the Android platform that can be found among smartphones, tablets, and more. Initial evaluation of the P2P protocol performance, using Zigbee modems, was conducted and representative results are provided in this paper.